2021
DOI: 10.4103/jod.jod_68_21
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Scientific Rating of Commercial Apps Available in India for Diabetes Prevention

Abstract: Objectives: We aimed to evaluate the quality of currently available health apps for prevention of type 2 diabetes among Asian Indians using validated rating scales. Materials and Methods: Using the keywords, “diabetes prevention,” “healthy lifestyle,” and “fitness,” a total of 1486 apps available in India via Google Play were assessed for eligibility by two independent reviewers. After initial screening using specific inclusion and exclusion criteria, 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Push notifications and weekly SMS text messages inviting check-in were also used to influence user engagement [26], herein defined by number of check-ins. This is also consistent with the findings from a systematic review [34] that assessed 15 commercial apps for diabetes prevention and found that the app that included the notification features for activity tips, goal progress tips, goals adjustment, and completed goals had the highest engagement mean score (4.5 points out of 5). However, we argue that push notifications should not be a one-size-fits-all solution because marketing research suggests that among app users, just 50% accept push notifications from their favorite app, and 30% disable all push notifications [35].…”
Section: Reasons For User Engagement Onboarding or Adherence To The Appsupporting
confidence: 88%
See 1 more Smart Citation
“…Push notifications and weekly SMS text messages inviting check-in were also used to influence user engagement [26], herein defined by number of check-ins. This is also consistent with the findings from a systematic review [34] that assessed 15 commercial apps for diabetes prevention and found that the app that included the notification features for activity tips, goal progress tips, goals adjustment, and completed goals had the highest engagement mean score (4.5 points out of 5). However, we argue that push notifications should not be a one-size-fits-all solution because marketing research suggests that among app users, just 50% accept push notifications from their favorite app, and 30% disable all push notifications [35].…”
Section: Reasons For User Engagement Onboarding or Adherence To The Appsupporting
confidence: 88%
“…Other potential barriers to adoption included a lack of early active engagement with participants to verify that they could install the app, no direct contact with health care professionals, and not enough interactive features. Indeed, as reported in another systematic review, being less informative and less interactive can lead to a very low engagement mean score [34].…”
Section: Barriers To User Engagement Onboarding or Adherence To The Appmentioning
confidence: 64%
“…Even for those not facing language or accessibility barriers, a lack of culturally diverse information, led to disengagement with prevention or management DHIs which included dietary management. A study of apps available in India for diabetes prevention also noted a lack of culturally relevant food data [29]. Existing resources on South Asian or global diets such as those produced by health charities and the NHS [30][31][32][33] present an opportunity to improve these offerings, although this is subject to health care professional awareness.…”
Section: Findings In Contextmentioning
confidence: 99%
“…The results suggested two apps ‘Google Fit: Health and Activity Tracking’ and ‘HealthifyMe—Diet plan, Health and Weight Loss’ as being user-friendly and reliable quality. 55 Nevertheless, substantial evidence on the efficiency of these apps is still lacking.…”
Section: Real-world Evidence On the Success Metrics Of Digital Techno...mentioning
confidence: 99%
“…71 A systematic study has reported HealthifyMe as being good quality and user-friendly for the prevention of T2D among Asian Indians. 55 A healthcare start-up, Orbuculum, uses AI on genomic data to forecast the risk of developing diabetes. 69 Wealthy, another venture, offers affordable AI-based digital diabetes coaching solution to motivate Indian patients with T2D for diabetes self-management and to improve their QoL.…”
Section: Real-world Evidence On the Success Metrics Of Digital Techno...mentioning
confidence: 99%